The effect of human capital, social capital and organization capital on organization success at Jordanian telecommunication companies - Abdul Malek, A. Tambi; Rashidah, Mohamad Ibrahim; MumenYasinMoshalesh, Al Dalaien (2020)
Nowadays, organizational success is a dominantly variable that posits vast chances and defiance’s to the decision making and staff of telecommunications. This study aimed at uncover the effect of human, social, and organization capital on organizational success in Jordan. The data proportionally collected from 234 managers of Telecommunication companies. This study used PLS-SEM.3 software in analyzing the data. The results concluded that human capital had a positive impact on organizational success; the social capital has negative effect on organization success, and the organizational capital has positive effect on organization success, however, the norms of human resources management had a positive impact on organizational success. The managerial implications indicated from results that the managers in telecommunications companies that human resources management has a substantial impact on organization success. Therefore, they need to fetch fundamental changes in human capital and human resources management for comprehensive development and organization success in Jordan.